Nursing practice in home care: the mediation of care by reflexivity - Angélica Mônica Andrade; Edna Aparecida Barbosa de Castro; Maria José Menezes Brito; Patrícia Pinto Braga; Kênia Lara Silva
ABSTRACT Objective: To analyze the practice of nurses in home care, considering the mediation of care by reflexivity. Method: Unique, qualitative case study, anchored in the dialectical framework. The participants were 13 nurses who work in home care in Minas Gerais. Data were obtained by participant observation and interview, and submitted to critical discourse analysis. Results: Nursing care at home involves the repetitions of everyday actions and a degree of unpredictability. Reflexivity, according to Schön's theoretical framework, emerges as a component of professional practice that leads to the practice of care as a continuous assessment of work, and also to reflection on the challenges imposed by conflicting situations. Reflexivity also stems from professionals' search for improvements in their practices. Final considerations: We identified the presence of actions and knowledge mobilized by the reflexivity of the nurse in the home care setting. The following were the elements of this reflexive practice: knowing-in-action, reflection-in-action and reflection reflection-in-action.